Dominating Role of an Unusual Magnetotactic Bacterium in the Microaerobic Zone of a Freshwater Sediment - Spring, Stefan (1993)
A combination of polymerase chain reaction-assisted rRNA sequence retrieval and fluorescent oligonucleotide probing was used to identify in situ a hitherto unculturable, big, magnetotactic, rod-shaped organism in freshwater sediment samples collected from Lake Chiemsee. Tentatively named “Magnetobacterium bavaricum,” this bacterium is evolutionarily distant from all other phylogenetically characterized magnetotactic bacteria and contains unusually high numbers of magnetosomes (up to 1,000 magnetosomes per cell). The spatial distribution in the sediment was studied, and up to 7 × 10(5) active cells per cm(3) were found in the microaerobic zone. Considering its average volume (25.8 ± 4.1 μm(3)) and relative abundance (0.64 ± 0.17%), “M. bavaricum” may account for approximately 30% of the microbial biovolume and may therefore be a dominant fraction of the microbial community in this layer. Its microhabitat and its high content of sulfur globules and magnetosomes suggest that this organism has an iron-dependent way of energy conservation which depends on balanced gradients of oxygen and sulfide.